Biallelic loss of function variant in the unfolded protein response gene PDIA6 is associated with asphyxiating thoracic dystrophy and neonatal‐onset diabetes. Issue 5 (17th February 2021) - Al‐Fadhli, Fatima M.; Afqi, Manal; Sairafi, Mona Hamza; Almuntashri, Makki; Alharby, Essa; Alharbi, Ghadeer; Abdud Samad, Firoz; Hashmi, Jamil Amjad; Zaytuni, Dimah; Bahashwan, Ahmed A.; Choi, Jin Huk; Peake, Roy W. A.; et al.
Abstract: Protein disulfide isomerase A6 (PDIA6) is an unfolded protein response (UPR)‐regulating protein. PDIA6 regulates the UPR sensing proteins, Inositol requiring enzyme 1, and EIF2AK3. Biallelic inactivation of the two genes in mice and humans resulted in embryonic lethality, diabetes, skeletal defects, and renal insufficiency. We recently showed that PDIA6 inactivation in mice caused embryonic and early lethality, diabetes and immunodeficiency. Here, we present a case with asphyxiating thoracic dystrophy (ATD) syndrome and infantile‐onset diabetes. Whole exome sequencing revealed a homozygous frameshift variant in the PDIA6 gene. RNA expression was reduced in a gene dosage‐dependent manner, supporting a loss‐of‐function effect of this variant. Phenotypic correlation with the mouse model recapitulated the growth defect and delay, early lethality, coagulation, diabetes, immunological, and polycystic kidney disease phenotypes. In general, the phenotype of the current patient is consistent with phenotypes associated with the disruption of PDIA6 and the sensors of UPR in mice and humans. This is the first study to associate ATD to the UPR gene, PDIA6 . We recommend screening ATD cases with or without insulin‐dependent diabetes for variants in PDIA6 . Abstract : Biallelic PDIA 6 inactivation is associated with asphyxiating thoracic dystrophy and neonatal diabetes.